Analytical Solution for One-Dimensional Transport of Particles considering Dispersion in Deposition Kinetics - Xingxin Chen; Xinran Zhang; Zhonghan Wu (Geofluids)
The study of particle transport in porous media is of great significance for pollution mitigation, grouting reinforcement, municipal solid waste landfill management, and groundwater exploitation. We developed an analytical solution for a corrected convection-dispersion model that takes into account the effects of dispersion on deposition kinetics with regard to the particle concentration decay type. The rationality and correctness of the solution were verified using time, distance, deposition coefficient, diffusion coefficient, and decay coefficient. As the time increased, the particle concentration increased from zero to the peak value, then decreased to zero. However, as distance increased, the peak value of particle concentration gradually decreased. The deposition coefficient affected the magnitude of the peak value and the distance corresponding to the peak value. In addition, the greater the attenuation coefficient, the smaller the peak value. Overall, our method’s prediction results showed that considering the effect of dispersion on deposition kinetics produces better results than when this is not considered.